Contribution of Massive Neutrino on Large Scale Structures - Dhungel, PR; Sharma, SK; Khanal, U (Scientific World, 2010)
Sizes and masses of the Neutrino Structures calculated with different combination of parameters involved has shown interesting variation with remarkable shifting of position of peak value. The peak position of (ξRH0/Resc) shifts from ξ = x/x0 = 0.847 to 1.632, where x = m/T. Accordingly, the peak of the mass of neutrino structures also shifts. Key words: Neutrino; Large scale structures; Free streaming; Jeans mass; Momentum distribution DOI: 10.3126/sw.v5i5.2646 Scientific World, Vol. 5, No. 5, July 2007 1-5